Conservation and Improvement Strategy for Fogera Cattle: A Lesson for Ethiopia Ingenious Cattle Breed Resource - Assemu Tesfa; Dilip Kumar; Solomon Abegaz; Getinet Mekuriaw (Advances in Agriculture)
The paper is initiated to design appropriate conservation strategies and breeding scheme for Fogera cattle breed that will be used as a guide for other Ethiopian indigenous cattle breed. Two types of data, on-farm and on-station, were used; the on-farm data was collected from three districts, namely, Fogera, Dera, and Bahir Dar Zuria; those are expected as the home of the breed. A total of 150 farmers, which are knowledgeable and having at least one cattle of Fogera phenotype in their herd, were purposively selected and interviewed. Additionally, farmer’s focus group discussion (FGD) was conducted to capture the historical background, population, and distribution of the breed. SPSS (version 16) and index method was used to analyze the quantitative and scoring data’s, respectively. A meeting at national and regional level was also conducted to evaluate the existing conservation strategy and to identify the major stakeholders for the strategy. The main reasons to conserve Fogera breed are due to presence of interrelated constraints, presence of unique traits of the breed, better attitude of farmers, and decreasing population trend of the breed. Community-based in situ conservation strategy, to ensure the participation of the community, was designed for the breed. With the conservation strategy, related activities like feed development, animal health interventions, market linkage, and development of cooperatives will be implemented to improve the working environment. The stakeholders that are identified as an actor in the strategy should realize their honest participation for the sustainability of conservation and improvement of the breed.